Bio-activities and Application of Avocado Seed Powder in Soft Biscuits - Nga, Tran Thi Huyen; Thuy, Nguyen Thu; Cong, Le Thi Nhi; Van, Nguyen Ngoc Khanh (VNU Journal of Science: Natural Sciences and Technology, 2026)
Avocado is a very popular plant, widely used in Vietnam and around the world. Its fruit contains a lot of nutrients beneficial for health. During the processing avocado, the seed (accounting for 13 to 24% of the total avocado fruit weight) is often discarded as agricultural waste that requires further processing. However, avocado seeds are also known to contain bioactive compounds such as procyanidins, phenolics, fatty acids, amino acids, and weak acids which exhibit antioxidant, antibacterial, hypoglycemic, anti-diabetic, and anti-hypertensive properties. These compounds were applied in various pharmaceutical, biotechnological, chemical, and food industries. This study evaluated the antibacterial ability of avocado seed extracts on Helicobacter pylori HP09 and Bacillus spp., showing the high antibacterial activity of ethyl acetate extract. Avocado seed powder has been studied as a way to partially replace wheat flour in making soft biscuits. The supplement ratio of avocado seed powder was 10% of the total wheat flour weight. The other ingredients also include eggs, sugar, oil, vanilla, wheat flour, cocoa powder. The cookies were baked at 160 °C for 15 minutes. The results showed that incorporating avocado seed powder into soft cookies maintained their nutritional value, flavor, and appeal, while also providing health benefits.